Endocrine disrupting and carcinogenic effects of decabromodiphenyl ether - Wang, Yi; Wang, Xinpei; Sui, Shaofeng; Liu, Zhiyan (Frontiers in Endocrinology, 2023)
As an important industrial flame retardant, decabromodiphenyl ether (BDE209) is widely exposed in China, the human serum level of BDE209 is trending upwards over years. Its toxic effects and health risks have become increasingly considered recently. The adverse effect of BDE209 on thyroid function is of particular concern because of its structural similarity to thyroid hormones. BDE209 has been reported to be an endocrine disrupting chemical and could disturb thyroid hormone homeostasis in vivo through several pathways. which might be associated with not only thyroid dysfunction but also thyroid cancer. This review is to highlight advances in the relevance studies of BDE209 and thyroid function and the underlying mechanism. We can provide a theoretical basis for the formulation of environmental health standards, and put forward comprehensive thinking on the future researches in related fields.